Augmented refrigerator magnets - Eardley, Rachel; Swan, Laurel; Sellen, Abigail; Taylor, Alex; Hodges, Steve; Wood, Ken; Williams, Lyndsay (NordiCHI 2006, 2006)
We describe a number of augmented fridge magnet concepts that support (i) organization and planning in households; (ii) reminding; and (iii) methods household members use to assign ownership to particular tasks, activities and artifacts. These concepts are derived from field investigations into everyday fridge use in home settings and specifically the interactional properties exhibited by magnets and fridge surfaces.